Safe drilling technology for ultra-deep gas wells with complex pressure systems using managed pressure and gas-venting density reduction - LI Tao, YANG Zhe, CHI Chongrong, NIE Zunhao, XU Zhikai, CHEN Xun, WANG Fei (Youqicang pingjia yu kaifa)
Marine carbonate oil and gas resources in the western Sichuan region of the Sichuan Basin are buried at depths exceeding 7 000 meters. Vertically, multiple hydrocarbon reservoirs exist, resulting in complex pressure systems where the coexistence of influx and loss may occur within the same open hole-section. When downhole complications arise, well control becomes challenging. In such cases, a contingency casing string must be run, which increases the number of casing intervals, prolongs the drilling cycle, and raises overall costs. To address this challenge, a targeted optimization of the wellbore structure was performed after setting the contingency casing. However, technical challenges persisted due to the coexistence of high- and low-pressure systems within a single open-hole section, and the presence of a narrow safe mud weight window. Based on a managed pressure and gas-venting density reduction process, and integrating formation gas seepage theory with wellbore flow dynamics, the migration patterns of natural gas in both the formation and annular space were analyzed. The research results showed that during the early stage of gas-venting density reduction under managed pressure, the gas influx rate declined rapidly, then gradually slowed and stabilized. This technique effectively released formation energy and reduced formation pressure, thereby helping to expand the safe mud weight window. The gas influx rate was identified as the main factor affecting well control safety. To ensure safe operations, the gas influx rate must not exceed the critical safe threshold. Based on both theoretical analysis and cost evaluation, the optimal duration for gas-venting density reduction was determined to be 10 days. Field applications were conducted in two wells targeting high-pressure formations in the Maokou Formation within the Shuangyushi Structure. Managed pressure and gas-venting operations successfully reduced the lower limit of the safe mud weight window by 0.16 g/cm3 and 0.40 g/cm3 respectively. These wells were drilled in combination with low-pressure reservoirs in the Qixia Formation. As a result, the casing program was simplified from six intervals to five, significantly reducing the drilling cycle and costs. This led to the development of a safe drilling technology for ultra-deep gas wells with complex pressure systems through managed pressure and gas-venting density reduction. The proposed method provides a valuable technical reference for wellbore structure optimization and safe drilling operations in similar ultra-deep, complex pressure environments.